URGENSI PEMBARUAN REGULASI KETERBUKAAN INFORMASI EMITEN DI PASAR MODAL INDONESIA DALAM MENGHADAPI TANTANGAN TATA KELOLA PERUSAHAAN BERBASIS ESG - Kadek Jaya Kusumantara; Paltiada Saragi; Monaliza Kalalembang; Deni Firwandi; Huske Dwi Gustian; Poltak Maruli Immanuel; Adolf Fictor (Honeste Vivere, 2026)
The rapid advancement of Environmental, Social, and Governance (ESG) standards has fundamentally shifted the paradigm of information disclosure across global capital markets, elevating sustainability into a core pillar of market integrity. However, Indonesia’s issuer disclosure regime—governed primarily by Law No. 8 of 1995 on Capital Markets and Financial Services Authority (OJK) Regulation No. 31/POJK.04/2015—remains focused on conventional financial metrics and lacks explicit obligations for ESG disclosures aligned with the ISSB’s IFRS S1 and IFRS S2 standards. This regulatory dissonance creates legal uncertainty and heightens the risk of corporate greenwashing. To address these vulnerabilities, this study critically evaluates the normative gaps separating national capital market regulations from emerging global sustainability benchmarks. Ultimately, it proposes a comprehensive regulatory reform model designed to systematically integrate mandatory ESG disclosure frameworks, thereby enhancing transparency, issuer accountability, and overall financial ecosystem resilience in Indonesia.